PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TGT BERBANTUAN KUIS FAMILY 100 UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII PADA MATERI EKOLOGI - Astrid Dwika Anggraini; Ahmad Qosyim (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
The low level of students’ learning outcomes in ecology indicates the need for innovative instructional strategies that can enhance student engagement and conceptual understanding. This study aims to describe the improvement of students’ knowledge learning outcomes, the implementation of the learning process, and students’ responses after the application of the Teams Games Tournament (TGT) cooperative learning model assisted by the Family 100 quiz in ecology learning. This research employed a quantitative approach using a pre-experimental method with a one-group pretest–posttest design. The research subjects consisted of 34 seventh-grade students of class VII-K at SMP Negeri 2 Krian in the 2025/2026 academic year. Data were collected through learning outcome tests, observation sheets of learning implementation, and student response questionnaires. The data were analyzed using the N-Gain calculation, the Shapiro–Wilk normality test, the paired sample t-test, and quantitative descriptive analysis. The results showed that the average pretest score of 49.00 increased to 68.65 in the posttest, with an average N-Gain score of 0.376 categorized as moderate. The hypothesis testing results indicated a significant difference between the scores before and after the treatment. The implementation of learning was categorized as very good, and students’ responses were highly positive. Therefore, the application of the TGT cooperative learning model assisted by the Family 100 quiz is effective in improving students’ knowledge learning outcomes in ecology.